Weak Deflection Angle, Hawking Radiation and Greybody Bound of Reissner-Nordstrom Black Hole Corrected by Bounce Parameter - Javed, Wajiha; Atique, Mehak; Pantig, Reggie C.; Övgün, Ali (Mdpi, 2023)
In this study, we probe the weak lensing by a Reissner-Nordstrom black hole corrected by bounce parameter in plasma and dark matter mediums. For this, the optical geometry and the Gibbons-Werner approach are utilized to obtain the bending angle in the weak field limitations. We examine that the impact of these mediums increases the black hole's bending angle. In addition, we graphically study the deflection angle of light with respect to the impact parameter and examine that the bounce parameter directly affects the angle. Further, we compute the Hawking radiation via a topological method involving two invariants and verify our obtained result with the standard method of calculating the Hawking temperature. In addition, we compute the greybody factor's bound of the black hole. Moreover, we analyze the bound graphically and observe that the bound shows convergent behavior. We also study that our attained results reduce the results of the Reissner-Nordstrom and Schwarzschild black holes by reducing the parameters. Finally, we probe how the bounce parameter affected the shadow radius and compared it to the shadow produced if the black hole is immersed in plasma. It is revealed that the rate at which the shadow radius changes with respect to r easily tends to zero under the effect of the bounce parameter, while the plasma merely increases the shadow radius.
Keywords: general relativity; bending angle; Gauss-Bonnet theorem; plasma medium; black hole; greybody; Hawking temperature